THE RELATIONSHIP OF FAMILY SUPPORT WITH THE LEARNING MOTIVATION OF FINAL SEMESTER NURSING STUDENTS - Devi Zhariyah, Tania; Puji Hastuti, Apriyani; Pitaloka Priasmoro, Dian (Jurnal Keperawatan Sriwijaya, 2026)
Aim: This study aims to determine the relationship between family support and the learning motivation of final semester nursing students at ITSK Dr. Soepraoen Hospital Malang. Method: The study used a quantitative design with a cross-sectional approach. The sample consisted of 114 final-semester nursing students at ITSK Dr. Soepraoen Hospital Malang, selected using stratified random sampling. Instruments included the Family Support Scale (FLS) questionnaire and Hamzah B. Uno's Theory. Data analysis was performed using the fisher test to identify the relationship between the two variables. Result: Most students indicated instrumental support (35.09%), and 47.37% indicated learning motivation as a path to achieving future goals. The fisher test showed a significant relationship between family support and nursing students' learning motivation (p-value 0.0001). The higher the family support, the greater the students' learning motivation. Conclusion: There is a significant relationship between family support and learning motivation in final-semester nursing students at ITSK Dr. Soepraoen Hospital, Malang. This finding emphasizes the importance of family involvement to maintain nursing students' motivation to learn, even though they live far from home.